Radiology IT: Applications Integration vs. Consolidation. - Kijewski, Peter (Journal of Digital Imaging, 2011)
The question of whether Radiology IT systems should be composed of multiple applications integrated using standard data exchange protocols, such as DICOM and HL7, or implemented using consolidation of applications and systems has been debated for the past 30 years. The adequacy of the former approach has become a burning issue because the demands on Radiology IT systems have increased greatly. We report here on the experience of the Radiology Information Technology (IT) implementation at the Memorial Sloan-Kettering Cancer Center (MSKCC) over the past 11 years; during this time, the weekly image accumulation rate increased from 100,000 to 2,000,000 images. During the implementation period, major difficulties were encountered, largely as a result of the inadequacies of the Radiology IT architecture widely used in the healthcare industry. The approach we chose to correct some of these difficulties has been consolidation of some of the multiple systems and applications. Three examples of systems consolidation are discussed: (1) converting a dual-tier image storage system to a single tier, (2) consolidation of Mammography reading into PACS, and (3) enabling 3D visualization and analysis on the PACS workstation. Nevertheless, substantial research and development are needed in order to proceed with more extensive systems consolidation and, thus, a more manageable IT installation.